Dictator style : lifestyles of the world's most colorful despots - York, Peter (San Francisco : Chronicle Books, 2005)
Running with the idea that our homes are where we are truly ourselves, Dictator Styles examines the frightening interior decorating tastes of some of history's most alarming despots - and proves that absolute power corrupts absolutely, right down to the drapes.
Porfirio Diaz -- Vladimir Lenin -- Joseph Stalin -- Benito Mussolini -- Adolf Hitler -- Josip Broz Tito -- Francisco Franco -- Juan Peron -- Nicolae Ceausescu -- Joseph-Desire Mobutu -- Ferdinand and Imelda Marcos -- Idi Amin -- Jean-Bedel Bokassa -- Saddam Hussein -- Manuel Noriega -- Slobodan Milosevic
Keywords: BIOGRAPHY; DICTATORS BIOGRAPHY